Anomalous Superficial Radial Nerve Innervation to the Ulnar Dorsum of the Hand in Korean Adults - 장현정; 박천웅; 조유나; 나동욱 (대한근전도 전기진단의학회지, 18(2), 2016)
Objective: The purpose of this study is to clarify the incidence of anomalous superficial radial innervation to the ulnar dorsum of the hand and anomalous innervation of the dorsal ulnar cutaneous nerve to the radial dorsum of the hand in Korean adults. Method: Nerve conduction studies were performed on 230 hands of 115 persons to identify anomalous innervations. Sensory nerve action potentials were recorded simultaneously using a 2-channel technique on both hands. Results: Anomalous innervation of the superficial radial nerve to the ulnar dorsum of the hand was observed in only 2 of the 230 hands of 115 persons, showing an incidence of 0.86%. Anomalous innervation of the dorsal ulnar cutaneous nerve to the radial dorsum of the hand was not found in any subject. Conclusion: This is the first study to report the incidence of anomalous superficial radial innervation to the ulnar dorsum of the hand in an Asian population. We found that the incidence of anomalous superficial radial innervation to the ulnar dorsum of the hand in Korean people was lower than that found in Western populations. KCI Citation Count: 0